Ecological Problems of Rivers at The Present Stage - Madraim Khasanovich Sarikulov; Bobirmirza Bakhtiyar o’gli Yusupov; Bakhodir Maratovich Bekimbetov (Scientific Trends, 2024)
This article examines the environmental problems of river pollution in various regions of the world at the present stage. An analysis of the problem of river pollution with various wastes and pollutants in different regions and countries of the world is given. The article examines the factors polluting rivers and the problems of drinking water shortage, and gives recommendations on maintaining the cleanliness of rivers. Currently, the most vulnerable part of nature and society has become the process of clogging river oases, which are often intensively polluted. Wastewater, pesticides, fertilizers, heavy metals and much more in huge quantities flow into rivers and lakes. According to experts, the level of pollution of such rivers as the Ganges, Mississippi, Rhine, Danube, Volga, as well as the Great American and other lakes exceeds the maximum permissible standards. According to experts, in some regions of the globe about 80% of all diseases are caused by poor quality drinking water. If we take into account that water intake structures and water pipelines, which, as a rule, receive water from open water bodies, show in samples almost 30 percent contamination, both in microbial and chemical terms, which in turn has a direct negative impact on the health of the population.
Keywords: Liquid waste, soil erosion, household garbage, red liquid, extremophile bacteria, dead zones, pathogenic microorganisms, thermal pollution.